Light-Emitting Diodes New Perspectives - Shakher Pathak, Chandra; Dadwal, Uday (IntechOpen, 2023)
This book provides a comprehensive overview of light-emitting diodes (LEDs). Chapters discuss micro-LEDs, nano-LEDs, high-power LEDs, and advancements in LED technology. It is a useful resource for a wide range of readers, including scientists, engineers, graduate students, postdoctoral fellows, and scientific professionals working in LEDs.